Evaluating the Efficacy of Transoral Robotic Surgery (TORS) Versus Radiotherapy, Chemotherapy, and Open Surgery in Treating Oropharyngeal Squamous Cell Carcinoma (OPSCC): A Systematic Review of Reviews - Abdulrhman Alsayeg; Maha Naif Alshammari; Abdulrahman Mesfer Alajmi; Reem Faihan Alotaibi (The Journal of Medicine, Law & Public Health, 2024)
Introduction: